Saint Jean Chrysostome à Antioche dans quatre homélies baptismales (dont BHG 1930w) - Devos, Paul (Analecta Bollandiana, 1991)
John Chrysostom, then still a priest, preached four baptismal catechisms at Antioch during the same Lent. The first three have just been published by Auguste Piédagnel (= Sources chrétiennes, 366), the fourth (BHG 1930w) having already been published in the same series by Antoine Wenger (= S. C., 50). We would date these catechisms to Friday, 10 March, Wednesday in Holy Week, 5 April, Maunday Thursday, 6 April, and Easter Sunday, 9 April 388.